No simple answers for the Finnish and Russian Karelia allergy contrast: Methylation of CD14 gene. Issue 7 (12th September 2016) - Khoo, Siew‐Kim; Mäkelä, Mika; Chandler, David; Schultz, En Nee; Jamieson, Sarra E.; Goldblatt, Jack; Haahtela, Tari; LeSouëf, Peter; Zhang, Guicheng
Abstract: Background: Finnish and Russian Karelian children have a highly contrasting occurrence of asthma and allergy. In these two environments, we studied associations between total serum immunoglobulin E (IgE) with methylation levels in cluster of differentiation 14 ( CD14 ). Methods: Five hundred Finnish and Russian Karelian children were included in four groups: Finnish children with high IgE (n = 126) and low IgE (n = 124) as well as Russian children with high IgE (n = 125) and low IgE (n = 125). DNA was extracted from whole blood cells and pyrosequenced. Three CpG sites were selected in the promoter region of CD14 . Results: Methylation levels in two of the three CpG sites were higher in the Finnish compared to Russian Karelian children. In the promoter area of CD14, the Finnish compared to Russian children with low IgE had a significant (p < 0.0001) increase in methylation levels at the Amp5Site 2. Likewise, the Finnish compared to Russian children with high IgE had a significant (p = 0.003) increase in methylation levels at the Amp5Site 3. In Russian children with low vs. high IgE, there were significant differences in methylation levels, but this was not the case on the Finnish side. In the regression analysis, adding the methylation variation of CD14 to the model did not explain the higher asthma and allergy risk in the Finnish children. Conclusions: The methylation levels in the promoter region of CD14 gene were higher in the Finnish compared to Russian Karelian children. However, the methylation variation of this candidate gene did not explain the asthma and allergy contrast between these two areas. Abstract :